Synthesis and Evaluation of Some 2-[(Substituted) ethanoyl]amino- 5-aryl-1,3,4-thiadiazoles as Diuretic Agents - K. Jain, Sanmati; Mishra, Pradeep (Asian Journal of Chemistry, 2010)
Twelve 2-[(substituted)ethanoyl]amino-5-aryl-1,3,4-thiadiazoles were prepared by the reaction of 2-(chloro ethanoyl)amino-5-aryl-1,3,4-thiadiazoles and various secondary amines. These compounds were screened for diuretic activity. The compounds namely 4a1, 4b2 and 4c2 showed good diuretic activity comparable with the standard drug acetazolamide at a dose level of 100 mg/kg, orally in albino rats.